2018
DOI: 10.1177/1748895818811891
|View full text |Cite
|
Sign up to set email alerts
|

Mind the step: A more insightful and robust analysis of the sentencing process in England and Wales under the new sentencing guidelines

Abstract: The ‘England and Wales Sentencing Guidelines’ aim to promote consistency by organizing the sentencing process as a sequence of steps, with initial judicial assessments subsequently adjusted to reflect relevant case characteristics. Yet, existing evaluations of the guidelines have failed to incorporate this structure adequately, instead concentrating solely on sentence outcomes. We use multivariate multilevel models to offer new insights into the decisions made throughout the sentencing process. Focusing on cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Nevertheless, omissions are likely since the variables included in the analysis depend on the information available in the case files; for example, we do not have information on potentially relevant factors such as ethnicity, economic situation, employment status or education. Moreover, access to more comprehensive data on cases processed in Spain could allow us to fit multilevel models that have been described as more insightful and robust for analysing the sentencing process (Pina-Sánchez et al, 2020). A further limitation is that our dataset does not provide insight into the underlying decision making of the different actors involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, omissions are likely since the variables included in the analysis depend on the information available in the case files; for example, we do not have information on potentially relevant factors such as ethnicity, economic situation, employment status or education. Moreover, access to more comprehensive data on cases processed in Spain could allow us to fit multilevel models that have been described as more insightful and robust for analysing the sentencing process (Pina-Sánchez et al, 2020). A further limitation is that our dataset does not provide insight into the underlying decision making of the different actors involved.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities have also been identified along racial lines, with some studies finding black people obtain less value for their pleas (Johnson and Hernandez, 2021; Metcalfe and Chiricos, 2018; Smith, 1986). Finally, the stage of the criminal process when the defendant enters the plea can impact the size of the discount, as early pleas have been associated with greater reductions in sentencing in the UK (Pina-Sánchez et al, 2020; Roberts and Bradford, 2015).…”
Section: Overview Of Extant Literature On ‘Plea Discounts’ or ‘Trial...mentioning
confidence: 99%
“…Wales 2017). Recent empirical studies have concluded that courts substantially follow this pattern in their sentencing decisions (Pina-Sánchez et al 2018, Roberts & Bradford 2015. This empowers police and prosecutors because defendants have incentives not to challenge the police's investigations or prosecutors' decisions and to shorten the pretrial judicial process as much as possible (McConville 2002, McEwan 2011.…”
Section: Langermentioning
confidence: 99%
“…Other researchers explored the attitudes of the general public, crime victims, witnesses, and offenders toward plea sentencing reductions, finding, for example, that there is more support for sentencing reductions for guilty pleas entered early in the criminal process (Dawes et al 2011). There has also been a recent wave of quantitative empirical studies on sentencing based on individual case-level data obtained from the release of judicial sentencing surveys; such studies have used multivariate regression analyses and concluded that almost all defendants that plead guilty receive a discount of one third or less, that these discounts largely comply with the sentencing discounts established by English law, and that there is no substantial evidence of disparity among the courts in sentencing, but there are some unwarranted sentencing disparities across cases among offense categories and other case or defendant characteristics (see, e.g., Pina-Sánchez et al 2018, Roberts & Bradford 2015.…”
Section: Empirical Studies Of Plea Bargaining and Other Trial-avoiding Mechanisms In Individual Jurisdictionsmentioning
confidence: 99%
“…those indicating seriousness) than to the additional aggravating and mitigating factors provided in ‘Step Two’ (Fleetwood et al, 2015; Irwin-Rogers and Perry, 2015; Lightowlers and Pina-Sánchez, 2017; Maslen, 2015; Pina-Sánchez and Grech, 2018). More recently, Pina-Sánchez et al (under review) found evidence that judges generally follow the step-sequence in the order prescribed within the guidelines. Specficially, they found that, for the most part, the case characteristics listed in Steps Two and Four of the guidelines were being used as originally intended.…”
Section: Sentencing Guidelines As Choice Architecturementioning
confidence: 99%